Moving Beyond the Brain: Transcutaneous Spinal Direct Current Stimulation in Post-Stroke Aphasia - Marangolo, Paola; Fiori, Valentina; Shofany, Jacob; Gili, Tommaso; Caltagirone, Carlo; Cucuzza, Gabriella; Priori, Alberto (Frontiers in Neurology, 2017)
Over the last twenty years, major advances in cognitive neuroscience have clearly shown that the language function is not restricted into the classical language areas but it involves brain regions, which had never previously considered. Indeed, recent lines of evidence have suggested that the processing of words associated to motor schemata, such as action verbs, modulates the activity of the sensorimotor cortex, which, in turn, facilitates its retrieval. To date, no studies have investigated whether the spinal cord, which is functionally connected to the sensorimotor system, might also work as an auxiliary support for language processing. We explored the combined effect of transcutaneous spinal direct current stimulation (tsDCS) and language treatment in a randomized double-blind design for the recovery of verbs and nouns in fourteen chronic aphasics. During each treatment, each subject received tsDCS (20min, 2mA) over the thoracic vertebra (10th vertebra) in three different conditions: 1) anodic, 2) cathodic and 3) sham while performing a verb and noun naming tasks. Each experimental condition was run in five consecutive daily sessions over three weeks. Overall, a significant greater improvement in verb naming was found during the anodic condition with respect to the other two conditions, which persisted at one week after the end of the treatment. No significant differences were present for noun naming among the three conditions. The hypothesis is advanced that anodic tsDCS might have influenced activity along the ascending somatosensory pathways, ultimately eliciting neurophysiological changes into the sensorimotor areas which, in turn, supported the retrieval of verbs. These results further support the evidence that action words, due to their sensorimotor semantic properties, are partly represented into the sensorimotor cortex. Moreover, they also document, for the first time, that tsDCS enhances verb recovery in chronic aphasia and it may represent a promising new tool for language treatment.